"I'm All of Everything That I Am": Constituting the Indigenous Woman, the White Woman, and the Audience in Eve Ensler's The Vagina Monologues - Williamson, Tara (Atlantis, 2009)
The author's analysis highlights the reinforcement of stereotypical images of native women in The Vagina Monologues. She suggests that alternative performances/performativities of the play would better challenge oppression and would foster a more complex understanding of race, class, and gender.